Examining the Influence of Prison Overcrowding and Rehabilitation Programmes on Effective Rehabilitation and Inmate Correction in Nigerian Prisons - May O. ESIRI; Mustapha ALIYU (International Journal of Psychosocial Rehabilitation, 2020)
Effectiveness of correctional institutions in receiving theoretical and empirical concern as it has much implication for the functionality of the society. This study examined the predictive relationship prison overcrowding and rehabilitation programmes independently have on effective rehabilitation and inmates correction in correctional institutions across Delta State, Nigeria. A cross-sectional survey design was adopted and data was collected with a self-administered questionnaire. Two hundred and eighty inmates and 30 staff members of the prisons participated in the study. Data analysis supported hypothesis one since overcrowding have a negative and significant influence on effective rehabilitation. The effect size statistics for the hypothesis was large and this is of practical value. Hypothesis two was not supported as rehabilitation programmes were observed to positively and significantly influence inmate correction. It was recommended that for correctional institutions to achieve the objective of reforming inmates, prison environment should not be frustrating to inmates and staff